FACTORS ASSOCIATED WITH DERMATITIS SYMPTOMS IN MOTORCYCLE WORKERS IN DELI TUA TIMUR VILLAGE IN 2025: FAKTOR – Age, work experience, personal hygiene, symptoms of dermatitisFAKTOR YANG BERHUBUNGAN DENGAN GEJALA DERMATITIS PEKERJA BENGKEL SEPEDA MOTOR KELURAHAN DELI TUA TIMUR TAHUN 2025 - muhraza siddiq; armanda prima; Evfy Septriani Br Ginting; Dela Sakinah Pandiangan (Jurnal Penelitian Kesmasy, 2026)
Occupational dermatitis is a skin disease that arises due to exposure to harmful substances or factors in the work environment while performing jobs. Symptoms of this disease include redness, heat, pain, blistering, and peeling of the skin. Irritant and allergic contact dermatitis are common types, with irritant contact dermatitis accounting for 80% and allergic contact dermatitis accounting for 14-20% of cases (Akbar, 2020). This study aims to determine the factors related to workers in motorcycle repair shops in Deli Tua Timur Village. The type of research is quantitative with observational methods and a cross-sectional approach. The population consisted of 60 workers, with a sample of 60 respondents. The analysis results showed a significant relationship between age and symptoms of dermatitis among motorcycle repair shop workers in Deli Tua Timur Village, with a p-value of 0.002 < 0.05. There was also a significant relationship between work experience and symptoms of dermatitis, with a p-value of 0.005 < 0.05, and a significant relationship between personal hygiene and symptoms of dermatitis, with a p-value of 0.002 < 0.05. Recommendations for workers to prevent dermatitis include maintaining good personal hygiene to reduce the risk of developing dermatitis. Workers who develop dermatitis should seek medical attention promptly at a nearby health center or clinic to prevent the condition from worsening. To prevent symptoms of dermatitis, motorcycle repair shop workers should use gloves when working to protect their skin from chemicals or oil, clean their hands with soap and water before eating, and regularly wash their clothes after work.